High NEFA concentrations around parturition are associated with delayed ovulations in grazing dairy cows - Giuliodori, Mauricio Javier (2011)
The objectives of this study were to assess indicators of metabolic status of grazing dairy cows around parturition, and the relationship between these indicators with the resumption of ovulations postpartum (ROP). Holstein multiparous cows (N=20) grazing on improved pastures and supplemented with concentrates were body condition scored and tail bled weekly from wk −2 through +9 related to parturition. Plasma samples were analyzed for nonesterified fatty acids (NEFA), leptin, insulin-like growth factor-1 (IGF-1) and progesterone (P4). Data were analyzed with mixed models, logistic regression, with receiver operator characteristic (ROC), and Cox regression analysis. Cows having Delayed Ovulation ([DO], ROP on week ≥5) had lower BCS, and higher NEFAs than cows having a normal ROP around parturition (BCS: 2.73±0.08 vs. 2.94±0.05, Pb0.05, and NEFA: 0.43±0.04 vs. 0.35±0.02 mM, Pb0.10, respectively). Also, DO cows had lower BCS than normal herdmates (2.59±0.10 vs. 2.99±0.06, Pb0.01) around time of ROP, but they had similar NEFA, leptin and IGF-1. The risk for DO increased as NEFA increased (0.4% and 0.5% per every increasing mM of NEFA in prepartum and postpartum, respectively). The ROC curve showed that NEFA (prepartum and postpartum) had areas of 0.85 and 0.80, and cut-off values of 0.39 and 0.47 mM. Finally, hazard for ROP increased as prepartum IGF-1 increased, and it decreased as postpartum NEFA increased. In conclusion, cows with lower BCS and higher prepartum and postpartum NEFA had higher odds for getting DO than herdmates with greater BCS and lower NEFA concentrations.